TINJAUAN KEAMANAN DAN KEHALALAN PENGEMASAN DESAIN KREATIF - Siregar, Maruli; Mardiah, Mardiah; Rahmawati, Siti Irma (Jurnal Ilmiah Pangan Halal, 2019)
Cooking oil is one of the food ingredients consumed by all levels of Indonesian society. People generally use cooking oil many times so that the risk to health. The purpose of this study was to test the quality of cooking oil after repeated use. The sampling method is using 4 types of packaging brand oil and 1 type of bulk oil each type of 1 liter. The frying oil sample taken was placed in a sealed bottle, inserted into a thermos, and brought to the laboratory for testing. Type of food used for frying is tempe and mackerel as much as 3 times the frying test. The frying method is deep frying. The analyzes were peroxide number, acid number, and water content. From the research, the characteristic of the quality of cooking oil average peroxide number in the first to third repetition is 0.63-5,63 meq / kg, acid number 0,22-0,56 mg KOH / g, and moisture content 0 , 05-0.18%. In the repetition of frying tempe until fifth cooking oil is above standard, while the frying tempe on the seventh repetition is above standard.Keywords: deep frying, quality, cooking oil.